Procedural Justice and Legitimacy in the Political Thought of John Rawls - Solís Porras, Pedro J. (2025)
The relationship between procedural justice and legitimacy is addressed based on the political thought of John Rawls. The idea that this relationship is direct but not necessarily strong is defended. Rawls is criticized for not sufficiently recognizing the non-instrumental values of procedural justice that can serve to legitimize political processes. Finally, the proposed theses are nuanced in the light of empirical findings.